A study on factors that lead to building collapse in Malaysia / Muhammad Rizham Mat Noor - Mat Noor, Muhammad Rizham (Faculty of Architecture, Planning and Surveying, 2013)
Building collapse incident is always became national issue in our country, Malaysia It is because when the accident happens, public is not been revealed the factors that cause the building collapses. There is also no consequence on the investigation of the problem. It is became more madness if the case is happened twice on same building. People will blame everyone in construction industry, politician, government and others because for them there is no action has been taken until the same problem happens again. This study is aimed to determine the factors lead building collapse accident in Malaysia Besides, to find out the factors of building collapse, an investigation must be taken. Therefore, this study isalso discussed about procedure or method of investigation to discover the causes of the accident. In order to make this academic study achieve its objectives, the research methodology that is implemented will be open-ended interviews, observation at site and sample of case studies. Furthermore, the data will be also collected from specific references such as journals, newspaper articles, reports, findings, books, thesis and internet. All the collected data will be discussed including method of investigation, finding based on interview and observation and review of past incidents. Based on finding, the recommendation to avoid building collapse in further is suggested. Thus, this study will highlight the problems of building collapse in Malaysia This academic study is concluded with a suggestion on methods that can be implemented in construction industry so that the problem will not occur again in future.